Detection of a Free Radical in the Primary Reaction of Chloroplast Photosystem II - Malkin, Richard (National Academy of Sciences, 1973)
Electron paramagnetic resonance (EPR) spectroscopy has revealed a new free-radical signal produced by illumination of spinach chloroplasts at 77°K. This signal is observed only when an oxidant (ferricyanide) is added to the chloroplast suspension in the dark before illumination. The EPR signal is produced at 77°K by illumination with 645-nm monochromatic light capable of activating Photosystem II but not with 715-nm illumination capable of activating Photosystem I. Furthermore, since the signal shows a relative increase in chloroplast fragments enriched in Photosystem II but is absent in chloroplast fragments enriched in Photosystem I, we conclude that this new EPR signal is associated with the primary photoact of Photosystem II in chloroplasts. On the basis of the measured EPR parameters (g = 2.0026 ± 0.0002, linewidth = 8 G), it is suggested that the signal may be associated with the reaction-center chlorophyll of Photosystem II.